Fermentasi kombucha bunga telang (Clitoria ternatea L) sebagai produk bioteknologi sederhana dalam memberikan reaksi farmakodinamik mencit (Mus musculus L) yang terpapar asap rokok dan morfometri ovarium - Dwiyarina Margarisa; Firman Rezaldi; Isti Dwi Pruschia; Muhammad Andry; M. Fariz Fadillah; Mutia Muhardiyanti; Hendra Jaya; Leni Halimatusyadiah; Muhammad Amin Nasution (Journal of Pharmaceutical and Sciences, 2023)
One of the fertility indicators in women is the optimal functioning of the ovaries. Exposure to cigarette smoke affects the decline in ovarian function in quality and quantity. The main components contained in cigarette smoke include tar, nicotine, carbon monoxide, inorganic gases, heavy metals, nitrosamines, carbonyls, formaldehyde, and polynuclear aromatic hydrocarbons. The main components contained in cigarette smoke positively influence female reproductive hormone levels and even reduce fertility. One of the efforts to prevent free radicals from cigarette smoke and have the potential as a natural antioxidant is consuming butterfly pea flower kombucha. The butterfly pea flower kombucha from previous studies contains phytochemicals that can inhibit free radicals. This study aimed to study the effect of butterfly pea flower kombucha on the ovary morphometry of female mice exposed to cigarette smoke. The design of this study was Completely Randomized Design (CRD). The test animals used were female mice aged 10 to 12 weeks weighing 20 to 20 g in a total of 24 mice. The butterfly pea flower kombucha given was ten mL/L, 20 mL/L, 30 mL/L, and 40 mL/L. Cigarette smoke exposure to mice was carried out on days 1-20 as much as one stick and treated with butterfly pea flower kombucha on days 21-40. Mating of female mice was carried out on the 40th day. Observations of ovarian morphometry such as length, width, weight, and number of corpus luteum were carried out on the 18th day of gestation. ANOVA and DMRT with a confidence level of 1% is the data analysis performed. The conclusion of this study was that butterfly pea flower kombucha had a good effect on improving fertility levels, which could be observed with test parameters such as length, width, weight, and number of corpus luteum and administration of kombucha with a concentration of 40 mL/L was the best treatment.